2020
DOI: 10.1093/jrr/rraa041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative chemoradiotherapy on the immunological status of rectal cancer patients

Abstract: The aim of the study was to investigate the effect of chemo-radiation on the genetic and immunological status of rectal cancer patients who were treated with preoperative chemoradiotherapy (CRT). The expression of immune response-associated genes was compared between rectal cancer patients treated (n = 9) and not-treated (n = 10) with preoperative CRT using volcano plot analysis. Apoptosis and epithelial-to-mesenchymal transition (EMT) marker genes were analysed by quantitative PCR (qPCR). Other markers associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
5
18
0
Order By: Relevance
“…Elevated expression of B7H3 has been found in serum of patients with malignant tumors, which is related to clinical stage and progression of cancer (49,50), since B7-H3 appears to be correlated with different proteins that contribute to tumor migration, invasion and angiogenesis (51,52). Besides, B7-H3 blocking in combination with chemotherapy is a promising treatment option based on preclinical animal studies (53). Currently, some previous studies have described a significant correlation between tumor expression of B7-H3 and prognosis (14,54), whereas, majority of them reported that high tumor B7-H3 expression was associated with more advanced disease (31), increased risk of recurrence (35) or shorter survival time (55), which was consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Elevated expression of B7H3 has been found in serum of patients with malignant tumors, which is related to clinical stage and progression of cancer (49,50), since B7-H3 appears to be correlated with different proteins that contribute to tumor migration, invasion and angiogenesis (51,52). Besides, B7-H3 blocking in combination with chemotherapy is a promising treatment option based on preclinical animal studies (53). Currently, some previous studies have described a significant correlation between tumor expression of B7-H3 and prognosis (14,54), whereas, majority of them reported that high tumor B7-H3 expression was associated with more advanced disease (31), increased risk of recurrence (35) or shorter survival time (55), which was consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…In 2020, Yasui et al published a study whose aim was to investigate the effect of chemoradiotherapy on the immunological status of rectal cancer patients who were treated with preoperative chemoradiotherapy. The results demonstrated that the expression of immune checkpoint genes, such as B7-H3 and B7-H5, was upregulated after chemoradiotherapy [ 113 ]. Therefore, it can be supposed that B7 family checkpoint molecules could be used as predictors of response to chemoradiotherapy in colorectal cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined changes in the TME to evalaute if our model recapatituates changes in the TME in response to RT in human patients. Pior work has show a significant increase in M2 macrophage polarization post RT 14 . Similarly, when examining the TME of mice with AKP endoluminal tumors we observed a signfiant increase in macrophage infiltration (detected by macrophage surface marker F4/80) and M2 polarization (CD206 + F4/80 + ), but not M1 (CD11c + F4/80 + ) ( Fig.…”
Section: Mainmentioning
confidence: 94%